Aberrant Fat Metabolism in Caenorhabditis elegans Mutants with Defects in the Defecation Motor Program - Sheng, Ming (PLoS One, 2015)
The molecular mechanisms by which dietary fatty acids are absorbed by the intestine, and the way in which the process is regulated are poorly understood. In a genetic screen for mutations affecting fat accumulation in the intestine of Caenorhabditis elegans, nematode worms, we have isolated mutations in the aex-5 gene, which encodes a Kex2/subtilisin-family, Ca(2+)-sensitive proprotein convertase known to be required for maturation of certain neuropeptides, and for a discrete step in an ultradian rhythmic phenomenon called the defecation motor program. We demonstrate that aex-5 mutants have markedly lower steady-state levels of fat in the intestine, and that this defect is associated with a significant reduction in the rate at which labeled fatty acid derivatives are taken up from the intestinal lumen. Other mutations affecting the defecation motor program also affect steady-state levels of triglycerides, suggesting that the program is required per se for the proper accumulation of neutral lipids. Our results suggest that an important function of the defecation motor program in C. elegans is to promote the uptake of an important class of dietary nutrients. They also imply that modulation of the program might be one way in which worms adjust nutrient uptake in response to altered metabolic status.